The Arctic Ocean in CMIP6 Models: Biases and Projected Changes in Temperature and Salinity - Khosravi, Narges; Wang, Qiang; Koldunov, Nikolay; Hinrichs, Claudia; Semmler, Tido; Danilov, Sergey; Jung, Thomas; Koldunov, Nikolay; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (AWI) Bremerhaven Germany; Hinrichs, Claudia; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (AWI) Bremerhaven Germany; Semmler, Tido; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (AWI) Bremerhaven Germany; Danilov, Sergey; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (AWI) Bremerhaven Germany; Jung, Thomas; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (AWI) Bremerhaven Germany (Earth's Future, 2022)
We examine the historical evolution and projected changes in the hydrography of the deep basin of the Arctic Ocean in 23 climate models participating in the Coupled Model Intercomparison Project Phase 6 (CMIP6). The comparison between historical simulations and observational climatology shows that the simulated Atlantic Water (AW) layer is too deep and thick in the majority of models, including the multi‐model mean (MMM). Moreover, the halocline is too fresh in the MMM. Overall our findings indicate that there is no obvious improvement in the representation of the Arctic hydrography in CMIP6 compared to CMIP5. The climate change projections reveal that the sub‐Arctic seas are outstanding warming hotspots, causing a strong warming trend in the Arctic AW layer. The MMM temperature increase averaged over the upper 700 m at the end of the 21st century is about 40% and 60% higher in the Arctic Ocean than the global mean in the SSP245 and SSP585 scenarios, respectively. Salinity in the upper few hundred meters is projected to decrease in the Arctic deep basin in the MMM. However, the spread in projected salinity changes is large and the tendency toward stronger halocline in the MMM is not simulated by all the models. The identified biases and projection uncertainties call for a concerted effort for major improvements of coupled climate models. Plain Language Summary: Coupled climate models are crucial tools for understanding and projecting climate change, especially for the Arctic where the climate is changing at unprecedented rates. A cold fresh layer of water (aka halocline) has been protecting sea‐ice at the surface from the warm layer of water (aka Atlantic Water layer) which flows underneath and could potentially accelerate sea ice melting from below. Climate change disturbs this vertical structure by changing the temperature and salinity of the Arctic Ocean (in a process known as Atlantification and Pacification) which may lead to additional sea ice basal melting and accelerate sea ice decline. We examined the ...